Discovery of C-3 Tethered 2-oxo-benzo[1,4]oxazines as Potent Antioxidants: Bio-Inspired Based Design, Synthesis, Biological Evaluation, Cytotoxic, and in Silico Molecular Docking Studies - Sharma, Vashundhra; Jaiswal, Pradeep K.; Saran, Mukesh; Yadav, Dharmendra Kumar; Saloni,; Mathur, Manas; Swami, Ajit K.; Misra, Sanjeev; Kim, Mi-hyun; Chaudhary, Sandeep (Frontiers in Chemistry, 2018)
The discovery of C-3 tethered 2-oxo-benzo[1,4]oxazines as potent antioxidants is disclosed. All the analogs 20a-20ab have been synthesized via “on water” ultrasound-assisted irradiation conditions in excellent yields (upto 98%). All the compounds have been evaluated for their in vitro antioxidant activities using DPPH free radical scavenging assay as well as FRAP assay. The result showed promising antioxidant activities having IC50 values in the range of 4.74 ± 0.08 to 92.20 ± 1.54 μg/mL taking ascorbic acid (IC50 = 4.57 μg/mL) as standard reference. In this study, compounds 20b and 20t, the most active compound of the series, showed IC50 values of 6.89 ± 0.07 μg/mL and 4.74 ± 0.08 μg/mL, respectively in comparison with ascorbic acid. In addition, the detailed SAR study shows that electron-withdrawing group increases antioxidant activity and vice versa. Furthermore, in the FRAP assay, eight compounds (20c, 20j, 20m, 20n, 20r, 20u, 20z, and 20aa) were found more potent than standard reference BHT (C0.5FRAP = 546.0 ± 13.6 μM). The preliminary cytotoxic study reveals the non-toxic nature of active compounds 20b and 20t in non-cancerous 3T3 fibroblast cell lines in MTT assay up to 250 μg/mL concentration. The results were validated via carrying out in silico molecular docking studies of promising compounds 20a, 20b, and 20t in comparison with standard reference. To the best of our knowledge, this is the first detailed study of C-3 tethered 2-oxo-benzo[1,4]oxazines as potential antioxidant agents.